2022
DOI: 10.25165/j.ijabe.20221501.6725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of droplet size and spray interval on root-to-shoot ratio, photosynthesis efficiency, and nutritional quality of aeroponically grown butterhead lettuce

Abstract: The proper selection of the atomizer (droplet size) and nutrient solution spray interval is one of the most important factors to be investigated in aeroponics systems for sustainable agriculture. The aim of this study was to research the effects of four aeroponics atomizing nozzles (one air-assisted; A 1 , two air-less; A 2 and A 3 , and one ultrasonic fogger; A 4 ) with droplet sizes of 11.24 µm, 26.35 µm, 17.38 µm, and 4.89 µm, respectively, four spray intervals (15 min (I 1 ), 30 min (I 2 ), 45 min (I 3 ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…Performa pengabutan larutan nutrsi dilakukan dengan cara membandingkan konsentrasi larutan pada wadah dengan konsentrasi yang dikabutkan oleh modul atomizer dengan menggunakan persamaan (1). Pengukuran performa mengacu pada persentase (%) perbandingan nilai luaran dengan nilai masukan sebuah unit, dalam hal ini konsentrasi larutan nutrisi (Tunio et al, 2022).…”
Section: Analisis Kinerja Ultrasonic Atomizer Dan Keragaan Tanamanunclassified
“…Performa pengabutan larutan nutrsi dilakukan dengan cara membandingkan konsentrasi larutan pada wadah dengan konsentrasi yang dikabutkan oleh modul atomizer dengan menggunakan persamaan (1). Pengukuran performa mengacu pada persentase (%) perbandingan nilai luaran dengan nilai masukan sebuah unit, dalam hal ini konsentrasi larutan nutrisi (Tunio et al, 2022).…”
Section: Analisis Kinerja Ultrasonic Atomizer Dan Keragaan Tanamanunclassified
“…In onion, total phenolic contents decreased as spraying duration increased, while total flavonoid contents generally increased [11]. Another research showed that the root length of better-head lettuce increased when the spraying interval is relatively short [13].…”
Section: Introductionmentioning
confidence: 96%
“…e level of antioxidant and sprout development were primarily affected by the spraying interval and duration [10]. In various plant species, the effects of the spraying interval and duration on the morphological and biochemical changes have been reported earlier [11][12][13]. In onion, total phenolic contents decreased as spraying duration increased, while total flavonoid contents generally increased [11].…”
Section: Introductionmentioning
confidence: 99%
“…In electrostatic spraying, the main factors affecting droplet deposition on crop leaf surface are charging voltage, spraying pressure, spraying height, droplet size, etc. [16][17][18].…”
Section: Introductionmentioning
confidence: 99%